2020
DOI: 10.3390/polym12102246
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on the Catalytic Degradation of Rhodamine B by Hydrogen Peroxide: Effect of Surfactant Coated and Non-Coated Iron (III) Oxide Nanoparticles

Abstract: Iron (III) oxide (Fe3O4) and sodium dodecyl sulfate (SDS) coated iron (III) oxide (SDS@Fe3O4) nanoparticles (NPs) were synthesized by the co-precipitation method for application in the catalytic degradation of Rhodamine B (RB) dye. The synthesized NPs were characterized using X-ray diffractometer (XRD), vibrating sample magnetometer (VSM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier transform infra-red (FT-IR) spectroscopy techniques and tested in the removal of RB. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The UV-vis region of electromagnetic radiation, which corresponds to the bandgap, highlights the bandgap in the visible range. Earlier research found a similar pattern of behavior [42][43][44].…”
Section: Photocatalytic Activitysupporting
confidence: 58%
“…The UV-vis region of electromagnetic radiation, which corresponds to the bandgap, highlights the bandgap in the visible range. Earlier research found a similar pattern of behavior [42][43][44].…”
Section: Photocatalytic Activitysupporting
confidence: 58%
“…Successful coating with citric acid is confirmed by the peaks at 1358 cm -1 and 1538 cm -1 , which can be attributed to COOstretching bands in citric acid [25,26] (see Figure 7b). FT-IR spectra for SDS-coated MNPs are presented in Figure 7c: the peak at 1351 cm -1 is assigned to the stretching vibration of the S=O band, while the peaks at 2973 cm -1 and 2876 cm -1 are attributed to the C-H bands [27,28] -all of which indicates successful MNP modification via SDS coating.…”
Section: Effects Of Mnp Modificationmentioning
confidence: 99%
“…[ 10–19 ] Interestingly, TiO 2 /Fe 3 O 4 composites are also effective photocatalysts for the activation of peroxymonosulfate (PMS) to form sulfate radical (SO 4 •− ), which provides a stronger oxidation ability and longer lifetime as compared to traditional hydroxyl radical (HO • ), thus providing the synergistic effect of adsorption, photocatalysis, and photocatalytic activation. [ 16,17,20 ] The use of TiO 2 /Fe 3 O 4 ‐based magnetic photocatalysts for the treatment of dyes in water has been reported in the literature, including photocatalysis (e.g., methylene blue (MB), [ 11,12 ] Rhodamine B (RhB), [ 21–23 ] methyl orange (MO), [ 24 ] and phenol [ 14 ] , and photocatalytic activation with H 2 O 2 (e.g., RhB [ 25 ] and MB [ 26 ] ) and PMS (e.g., food dyes [ 15 ] ). From the published works, TiO 2 /Fe 3 O 4 is a potential catalyst in wastewater treatment, especially with complex pollutant compositions such as textile dyeing wastewater.…”
Section: Introductionmentioning
confidence: 99%